Selective Enrichment of Munc13-2 in Presynaptic Active Zones of Hippocampal Pyramidal Cells That Innervate mGluR1α Expressing Interneurons - Holderith, Noemi; Aldahabi, Mohammad; Nusser, Zoltan (Frontiers in Synaptic Neuroscience, 2022)
Selective distribution of proteins in presynaptic active zones (AZs) is a prerequisite for generating postsynaptic target cell type-specific differences in presynaptic vesicle release probability (Pv) and short-term plasticity, a characteristic feature of cortical pyramidal cells (PCs). In the hippocampus of rodents, somatostatin and mGluR1α expressing interneurons (mGluR1α+ INs) receive small, facilitating excitatory postsynaptic currents (EPSCs) from PCs and express Elfn1 that trans-synaptically recruits mGluR7 into the presynaptic AZ of PC axons. Here we show that Elfn1 also has a role in the selective recruitment of Munc13-2, a synaptic vesicle priming and docking protein, to PC AZs that innervate mGluR1α+ INs. In Elfn1 knock-out mice, unitary EPSCs (uEPSCs) in mGluR1α+ INs have threefold larger amplitudes with less pronounced short-term facilitation, which might be the consequence of the loss of either mGluR7 or Munc13-2 or both. Conditional genetic deletion of Munc13-2 from CA1 PCs results in the loss of Munc13-2, but not mGluR7 from the AZs, and has no effect on the amplitude of uEPSCs and leaves the characteristic short-term facilitation intact at PC to mGluR1α+ IN connection. Our results demonstrate that Munc13-1 alone is capable of imposing low Pv at PC to mGluR1α+ IN synapses and Munc13-2 has yet an unknown role in this synapse.